Suggestion of integrated trolley system in Kuala Lumpur International Airport / Khairul Anuar Mahmood@Talib and Shaiful Bakhtiar Ahmad - Mahmood@Talib, Khairul Anuar; Ahmad, Shaiful Bakhtiar (2000)
For the completion of the diploma in Mechanical Engineering course, a final project must be done. The project must be based on the requirement and the syllabus of the course that we are enrolled in. Consequently, we have prepared this project entitled 'Suggestion Of Integrated Trolley System In KUA'. There is no man-made system that is fully perfect. Consequently, every system has to be checked and renewed always to keep track with current development Our project advisor Puan Che Faridah Mat Taib has taken initiative to determine the problems faced by the trolley system in KLIA. We are to do the work conducting the research relating to the above problems and proposing an alternative system should it be needed. The focus of the project is on the trolley system in KLIA. Moreover it considered ideas that can be adapted from other systems avalaible in wholesalers' stores and other places to form a system that not only maintain the advantages offered by the old system but also overcome its problems. Since the period of the project was just one semester, the research done was limited to explanation about the alternative trolley system as a whole and its combination with Total Airport Management System (TAMS). The project commercial value was also considered since it determines the success of the project. Hopefully, this project will benefit anyone who wishes to apply it.